Electrophoretically Deposited Polymeric Films: Evidence of Correlation between Electrochemical Impedance Spectroscopy Measurements and Morphological Properties. Issue 11 (1st January 2015) - De Riccardis, M. F.; Carbone, D.; Capodieci, L.
Abstract : Electrochemical Impedance Spectroscopy (EIS) was used in order to investigate coatings obtained by Electrophoretic Deposition (EPD) from a morphological point of view. The analyzed samples were made of polyetheretherketone (PEEK), also mixed with alumina or polytetrafluoroethylene (PTFE), and were characterized by different thickness, porosity and roughness. For each kind of samples, a suitable equivalent circuit was used to interpolate EIS spectra. A linear correlation between thickness and Rcoat of PEEK coatings was found, whereas an exponential correlation between Cdl and thickness and porosity was observed for PEEK-Alumina composite coatings. Moreover, when the coating roughness was the most relevant feature, a Warburg element (with an impedance equal to ZCPE = A/(jω) n ) was inserted in the equivalent circuit. In this case, the roughness was inversely correlated with n . These results indicate that electrochemical impedance spectroscopy can be used as a non-destructive technique to evaluate, at least qualitatively, the main morphological characteristics of EPD coatings.